2018
DOI: 10.4172/2157-7595.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and Hypertension: A Systematic Review

Abstract: Introduction:The objective of this systematic review is to study the effects of yoga in reducing blood pressure in adult patients with hypertension. Yoga is universally accepted as ancient practice in which you use breathing techniques, exercise and mediation. Yoga is increasing being practiced in studios and is widely being accepted as part of a wellness program in corporate companies. The focus of this literature review is to provide a summary and evaluation of the existing research and gain a new body of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Several systematic reviews have evaluated and synthesized evidence on the effectiveness of yoga interventions for managing hypertension ( 10 , 20 , 29 35 ). Previous reviews showed that yoga interventions significantly reduced SBP and DBP ( 10 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews have evaluated and synthesized evidence on the effectiveness of yoga interventions for managing hypertension ( 10 , 20 , 29 35 ). Previous reviews showed that yoga interventions significantly reduced SBP and DBP ( 10 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews showed that yoga interventions significantly reduced SBP and DBP ( 10 , 32 , 33 ). Six of these reviews, despite claiming to include studies conducted on patients with hypertension and yoga interventions, included studies where not all the participants were hypertensive ( 10 , 29 , 30 , 34 ), yoga interventions were part of multimodal interventions ( 10 , 29 , 35 ) or interventions other than yoga were assessed ( 30 , 33 ). In addition, though these systematic reviews suggested that yoga might be effective in hypertension management, they were inconclusive.…”
Section: Introductionmentioning
confidence: 99%